Tailored Screening for Late-Life Depression: A Short Version of the Teate Depression Inventory (TDI-E) - Balsamo, Michela; Saggino, Aristide; Carlucci, Leonardo (Frontiers in Psychology, 2019)
A host of geropsychiatric measures have been developed for diagnostic purposes but most showed several weaknesses, such as the time-consuming administration, the development and validation in younger populations, and the lack of discrimination between anxiety and depression. Among the extant self-report measures of depression, the Teate Depression Inventory (TDI; Balsamo & Saggino, 2013), developed via Rasch analysis, showed a satisfactory level of diagnostic accuracy and allowed the reduction of false positives in test scoring in clinical and non-clinical samples, as well as across the lifespan. The present study aimed at refining this Rasch-based depression questionnaire for elderly. It was administered to a sample of 836 elderly people (49.5% males; mean age = 73.28; SD=6.56). Through a step-by-step Rasch analysis process, the refinement process resulted in a shorter unidimensional set of the best-fitting and discriminative 9 items from the full form: It showed good internal construct validity, with unidimensional structure, local dependency, good reliability (Person Separation Index and Cronbach alpha), and no signs of Differential Item Functioning due to gender and age (65 vs 75+ years). This abbreviated measure, named TDI-Elderly (TDI-E), displayed comparable psychometric quality of the longer form. Cut-off points and normative data provided. The latter could offer important advancements for the interpretation of the questionnaire scores and enhance its usefulness for clinical and research applications, also when the TDI-E scores were comparable to the scores derived from other geriatric measures, even developed within the Classical Testing Theory.